DFNA5: hearing impairment exon instead of hearing impairment gene?. Issue 6 (1st June 2004) - Van Laer, L; Vrijens, K; Thys, S; Van Tendeloo, V F I; Smith, R J H; Van Bockstaele, D R; Timmermans, J-P; Van Camp, G
Abstract : Background: Three mutations in the DFNA5 gene have been described in three families with autosomal dominant non-syndromic hearing impairment. Although these mutations are different at the genomic DNA level, they all lead to skipping of exon 8 at the mRNA level. We hypothesise that hearing impairment associated with DFNA5 is caused by a highly unusual mechanism, in which skipping of one specific exon leads to disease that is not caused by other mutations in this gene. We hypothesise that this represents a very specific "gain of function" mutation, with the truncated protein exerting a deleterious new function. Methods: We performed transfection experiments in mammalian cell lines (HEK293T and COS-1) with green fluorescent protein (GFP) tagged wildtype and mutant DFNA5 and analysed cell death with flow cytometry and fluorescence microscopy. Results: Post-transfection death of HEK293T cells approximately doubled when cells were transfected with mutant DFNA5 –GFP compared with wildtype DFNA5–GFP. Cell death was attributed to necrotic events and not to apoptotic events. Conclusion: The transfection experiments in mammalian cell lines support our hypothesis that the hearing impairment associated with DFNA5 is caused by a "gain of function" mutation and that mutant DFNA5 has a deleterious new function.